Konsep Relationships Tourism dalam Pariwisata Maluku Berbasis Kearifan Lokal - Noviawan Rasyid Ohorella; Edi Prihantoro (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Tourism is currently the leading sector of the Indonesian government which is packaged in the context of local wisdom. One of the concepts that can raise local wisdom is the concept of relationships tourism. This study aims to identify and analyze the concept of relationships tourism in promoting Maluku tourism based on local wisdom. The method used is a qualitative descriptive approach, in which the researcher conducts involved observations, in-depth interviews, FGDs, and documentation of the object under study. The theory used is the Social Construction of Reality. The results showed that one of the Maluku tourism strategies was to develop the concept of relationships tourism in introducing local wisdom. One of the activities is that tourists are invited directly to live with local communities and carry out activities such as making processed grilled sago with traditional cooking utensils or playing traditional musical instruments on the beach. This is done to encourage Maluku tourism based on local wisdom.